Dimethyl fumarate improves white matter function following severe hypoperfusion: Involvement of microglia/macrophages and inflammatory mediators. Issue 8 (August 2018) - Fowler, Jill H; McQueen, Jamie; Holland, Philip R; Manso, Yasmina; Marangoni, Martina; Scott, Fiona; Chisholm, Emma; Scannevin, Robert H; Hardingham, Giles E; Horsburgh, Karen
The brain's white matter is highly vulnerable to reductions in cerebral blood flow via mechanisms that may involve elevated microgliosis and pro-inflammatory pathways. In the present study, the effects of severe cerebral hypoperfusion were investigated on white matter function and inflammation. Male C57Bl/6J mice underwent bilateral common carotid artery stenosis and white matter function was assessed at seven days with electrophysiology in response to evoked compound action potentials (CAPs) in the corpus callosum. The peak latency of CAPs and axonal refractoriness was increased following hypoperfusion, indicating a marked functional impairment in white matter, which was paralleled by axonal and myelin pathology and increased density and numbers of microglia/macrophages. The functional impairment in peak latency was significantly correlated with increased microglia/macrophages. Dimethyl fumarate (DMF; 100 mg/kg), a drug with anti-inflammatory properties, was found to reduce peak latency but not axonal refractoriness. DMF had no effect on hypoperfusion-induced axonal and myelin pathology. The density of microglia/macrophages was significantly increased in vehicle-treated hypoperfused mice, whereas DMF-treated hypoperfused mice had similar levels to that of sham-treated mice. The study suggests that increased microglia/macrophages following cerebral hypoperfusion contributes to the functional impairment in white matter that may be amenable to modulation by DMF.